A Review of Patient Lifting Interventions to Reduce Health Care Worker Injuries. (June 2015) - Aslam, Imran; Davis, Scott A.; Feldman, Steven R.; Martin, Willis E.
Health care workers suffer from musculoskeletal disorders at a significantly higher rate than workers in other industries. Consequently, a growing demand for patient handling devices to reduce worker injury has evolved. This article reviews the literature regarding interventions designed to reduce injuries among health care workers. A PubMed search was conducted using the terms "occupational health [Mesh Terms] patient lifting." Fourteen articles were identified that assessed interventions to improve worker safety. Of the 14 articles, 7 discussed technological interventions, 4 educational approaches, and 3 policy change. All three types of interventions were generally effective at improving worker safety, with the ideal intervention consisting of elements of all three types. Although adopting a new intervention may be expensive, the reduction in workers' compensation costs associated with injured nurses can easily outweigh the costs of interventions.